PENILAIAN TINGKAT KERENTANAN SUMBER DAYA AIR TERHADAP VARIABILITAS IKLIM DI DAS AESESA, PULAU FLORES, NUSA TENGGARA TIMUR - Eko Pujiono (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2015)
This study aimed to assess the level of  vulnerability of  water resources on the climate variability of  Aesesa Watershed, NTT Province. Vulnerability assessments using IPCC concept, where the vulnerability as a function of  exposure, sensitivity and adaptive capacity. Criteria and indicators of  those function were obtained from previous studies, then given a score and weighting in accordance with the degree of  importance, spatially display and overlay, to produce vulnerability map. The results showed that the trend of  annual temperature in the upper watershed in recent years is decreased, while in the middle and lower areas are increased. The annual precipitation showed an  trend in the , while in the middle and  showed a declining trend. increasing upper area lower areas Related to water resources, the river's stream flows are relatively stable in the last five years. Water quality assessment in the river is categorized as lightly polluted in the upstream and moderately polluted in the downstream. Based on vulnerability map, the watershed is classified into highly vulnerable (54%), moderately vulnerable (13%) and lowly vulnerable (33%). Such results could be useful for the Watershed Authority and other stakeholders to establish strategies, plans and actions for addressing problems on vulnerability of  water resource.